2008
DOI: 10.1177/172460080802300104
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 *2B and *4 Polymorphisms are associated with Lung Cancer Susceptibility in Mexican Patients

Abstract: The results of the study indicate a significant association between *2B/*2B and *4/*4 genotypes and the risk of developing lung cancer among Mexicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…This association depends on the number of cigarettes smoked per day and exposure time; however, in most studies, these parameters are not considered. In this regard, in our study, patients with stage III–IV tumors who smoked had increased risk, and our data are consistent with previous reports [ 39 , 40 ]. Also, the presence of lymph node metastases and chemotherapy type were risk factors for BC patients with stage III–IV tumors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This association depends on the number of cigarettes smoked per day and exposure time; however, in most studies, these parameters are not considered. In this regard, in our study, patients with stage III–IV tumors who smoked had increased risk, and our data are consistent with previous reports [ 39 , 40 ]. Also, the presence of lymph node metastases and chemotherapy type were risk factors for BC patients with stage III–IV tumors.…”
Section: Discussionsupporting
confidence: 93%
“…When the BC group was stratified by tumor stage, as either I–II or III–IV, and compared with the clinical and biochemical characteristics of BC, early menarche (7–10 years), contraceptive hormonal use, familial history, tobacco consumption, metastasis to lymph nodes, and chemotherapy type (FEC) emerged as risk factors. The association of tobacco use with BC is still controversial, and one study showed that smokers had a BC risk of 10–20% compared to nonsmokers [ 38 40 ]. This association depends on the number of cigarettes smoked per day and exposure time; however, in most studies, these parameters are not considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for m4 polymorphism, possible associations have been documented between the A allele and risk for lung cancer (Gallegos-Arreola et al, 2008;Shah et al, 2008;Ezzeldin et al, 2017), laryngeal squamous cell carcinoma (Gajecka et al, 2005) and thyroid cancer (Siraj et al, 2008). No association has been observed between m4 polymorphism and breast, colorectal, and gastric cancer (Li et al, 2004;Singh et al, 2007;Amrani et al, 2016, Little et al, 2006Agudo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time to our knowledge that this allele has been related to high lung cancer risk in a Caucasian population, since similar results have only been observed in Indians [37], African-Americans [38] or Hispanics [39]. In Caucasians, Vineis et al recently detected a positive allele-disease association, but only where the variant occurred in combination with a number of other CYP1A1 and GST polymorphisms [21].…”
Section: Discussionmentioning
confidence: 65%